(untitled) (Revista Cientifica Ingenio Magno, 2024)
The computational fluid dynamics simulation presented shows the behavior of the PC+ABS blends during the injection phase through a transient analysis of the injection molding process. The Fluent® computational fluid dynamic analysis module of Ansys Workbench® makes it possible to know the behavior of the injected material according to its properties and the design of the geometry of the injected product, represented by the mold cavities (fluid domain). The implementation of simulation allows engineers and processors to efficiently analyze the filling phase from early design stages due to obtaining the results of maximum filling pressure, visualization of the polymer flow front, pressure increase at the inlet, and the temperature of the flow front at the end of the injection phase. In conclusion, the computational simulation generates a prior understanding of the filling phase while minimizing the failures found until the advanced stages of production (injection mold and injected product manufactured). In addition, it guarantees the reduction of time and costs of the injection molding process through a completely computer-assisted environment.